The Role of Agile Human Resource Management and Adaptive Organizational Culture in Achieving Organizational Competitive Advantage in the Era of Technological Disruption - Achmad Mohyi (PT FORMOSA CENDEKIA GLOBAL, 2026)
The era of technological disruption requires organizations to continuously adapt to increasingly dynamic and complex market conditions. Digital transformation demands not only the adoption of advanced technologies but also the development of agile managerial practices and adaptive organizational cultures. This study examines the influence of Agile Human Resource Management (HRM) and Adaptive Organizational Culture on organizational competitive advantage in technology companies in East Java. A descriptive quantitative approach was employed using a survey method, with data collected through Likert-scale questionnaires from technology companies that have implemented agile HRM practices and adaptive cultural values. The data were analyzed using SPSS version 25, including reliability, normality, multicollinearity, heteroscedasticity tests, partial t-tests, and the coefficient of determination (R²). The findings reveal that Agile HRM has a positive and significant effect on competitive advantage by enhancing adaptability, collaboration, and operational efficiency. Similarly, Adaptive Organizational Culture significantly contributes to competitive advantage by fostering flexibility, continuous learning, innovation, and cross-functional collaboration. The R² results indicate that both variables jointly explain a substantial proportion of the variance in organizational competitive advantage.